Product Market Regulation In Romania : A Comparison With OECD Countries - Fay, Marianne (The World Bank, 2007)
Less restrictive product market policies are crucial in promoting convergence to higher levels of GDP per capita. This paper benchmarks product market policies in Romania to those of OECD countries by estimating OECD indicators of Product Market Regulation (PMR). The PMR indicators allow a comprehensive mapping of policies affecting competition in product markets. Comparison with OECD countries reveals that Romania's product market policies are less restrictive of competition than most direct comparators from the region and not far from the OECD average. Nonetheless, this achievement should be interpreted in light of the fact that PMR approach measures officially adopted policies. It does not capture implementation and enforcement, the area where future reform efforts should be directed if less restrictive policies are to have an effective impact on long-term growth prospects